Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/1361-6528/aaf12b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic structure of single-walled carbon nanotube by high-pressure H2 exposure

Abstract: We report on an electronic structure change of single-walled carbon nanotube (SWNT) on hexagonal boron nitride due to electron doping via high-pressure H 2 exposure. The fractional coverage of hydrogenated carbon atom is estimated to be at least θ=0.163 from the in situ I ds -V g measurements of the release process. Raman spectroscopy and x-ray photoelectron spectroscopy were carried out to support the in situ electrical measurements. In particular, we used the dissociative Langmuir-type model to yield the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As the (110)/(200) β ‐phase peak position does not shift after ZnO attachment to the PVDF‐TrFE EFs and subsequent hydrothermal treatment step, it can be concluded that the hydrothermal solution growth method is undertaken at a low enough temperature to not affect the PVDF‐TrFE crystal structure. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the (110)/(200) β ‐phase peak position does not shift after ZnO attachment to the PVDF‐TrFE EFs and subsequent hydrothermal treatment step, it can be concluded that the hydrothermal solution growth method is undertaken at a low enough temperature to not affect the PVDF‐TrFE crystal structure. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…An essential requirement for the advancement of continuous long‐term wearable devices is for electronics to be self‐powered and space‐efficient, without the need for bulky unsustainable batteries. Methods of self‐powering in research literature have included using materials that can harvest energy from the human body and ambient environment [ 20 ] (e.g., from light, [ 21 ] heat, [ 22,23 ] or mechanical force [ 24,25 ] ). In certain instances, energy harvesters can be used as active transducers for passive sensing by correlating the external stimuli (such as strain, [ 26–28 ] bending, [ 29 ] and impact force [ 30–34 ] ) to the generated output.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations